Evaluation of clinical and neonatal outcomes of cancer in pregnancy and patients in remission (Annals of Medical Research, 2026)
Aim: To retrospectively examine patients diagnosed with cancer during pregnancy and compare the maternal and natal outcomes of these patients with those in cancer remission and healthy pregnant women.Materials and Methods: This study was designed at a single tertiary care center. A total of 99 patients were included, of whom 18 were diagnosed with cancer during pregnancy, 21 had a pregestational history of cancer and were in remission, and 60 were healthy controls.Results: Breast cancer was the most frequently detected malignancy during pregnancy. The average cancer during pregnancy was seen at the 21st week. Diagnostic methods included various biopsy methods and magnetic resonance imaging. Some patients underwent cancer-related surgery and chemotherapy during pregnancy. Two patients diagnosed with cancer during pregnancy died. Neonatal and maternal intensive care requirements were found to be higher in patients diagnosed with cancer during pregnancy compared to the other two groups. Additionally, neonatal birth weight was lower than that observed in healthy pregnancies. Conclusion: We consider the monitoring and management of patients diagnosed with cancer during pregnancy to be a critical issue for ensuring optimal maternal and fetal health outcomes, and we emphasize the need for further research in this field.
Keywords: Active cancer during pregnancy; Maternal mortality; Neonatal intensive care requirements